Monitoramento elétrico de prédios utilizando processamento de eventos complexos - Jung, Fabiano Lucas (2025)
In the scope of smart cities, one of the sub themes of smart cities is smart buildings, where electrical monitoring is essential for the operation of the entire building and its associated applications. This work searched for ways to enhance and increase the speed of the diagnosis of electrical issues in buildings on the main campus of the University of Passo Fundo by implementing a complex event processing system. A data collection firmware was developed to gather electrical data via RS485 serial communication. In which multiple Kron Mult-k 05 meters are sequentially read, and the data is sent over the network to a BackEnd service with a REST API and complex event processing (CEP). In this stage, each collected event is inserted into the complex event processing engine, generating alerts. The engine used in the project was Drools. This work describes the configuration process, base rule structure, and final defined rules. A user interface was also developed for the university’s electrical systems department team to visualize, analyze, and validate the output of the event processing in the form of alerts and raw data. The work was validated through field data collection, where a hardware prototype was installed in one of the university’s power substations. Additionally, a Python-based simulator was used to trigger rules without relying on external factors. The results showed that the system operated within the expected time frames, and rules were triggered as intended. However, under normal field conditions, no alerts requiring corrective actions from the electrical systems team were triggered.